2018
DOI: 10.1097/j.pain.0000000000001212
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL2 and its receptor CCR2 in the dorsal root ganglion contribute to oxaliplatin-induced mechanical hypersensitivity

Abstract: Activation of innate immune mechanisms within the dorsal root ganglion and spinal dorsal horn has been shown to play a key role in the development of neuropathic pain including paclitaxel-related chemotherapy-induced peripheral neuropathy (CIPN). Here, we tested whether similar mechanisms are generalizable to oxaliplatin-induced CIPN. After a single intraperitoneal injection of 3 mg/kg oxaliplatin, mechanical withdrawal threshold and the expression of C-C chemokine ligand 2 (CCL2) and its receptor, CCR2, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 72 publications
5
46
1
1
Order By: Relevance
“…Among these cytokines, CCL2, CCL4 and CCL7, like CCL3 and CCL6, seem to also be important for the maintenance of neuropathy, and higher levels were still noted on the 28th day post‐CCI. Importantly, there is evidence that the above‐mentioned chemokines are also up‐regulated in other models of neuropathic pain, such as partial sciatic nerve ligation, oxaliplatin‐induced mechanical hypersensitivity and paclitaxel‐induced mechanical allodynia . We observed that CCL5 remained unchanged at the spinal cord level and was down‐regulated in the DRG.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Among these cytokines, CCL2, CCL4 and CCL7, like CCL3 and CCL6, seem to also be important for the maintenance of neuropathy, and higher levels were still noted on the 28th day post‐CCI. Importantly, there is evidence that the above‐mentioned chemokines are also up‐regulated in other models of neuropathic pain, such as partial sciatic nerve ligation, oxaliplatin‐induced mechanical hypersensitivity and paclitaxel‐induced mechanical allodynia . We observed that CCL5 remained unchanged at the spinal cord level and was down‐regulated in the DRG.…”
Section: Discussionmentioning
confidence: 53%
“…Importantly, there is evidence that the above-mentioned chemokines are also up-regulated in other models of neuropathic pain, such as partial sciatic nerve ligation, oxaliplatin-induced mechanical hypersensitivity and paclitaxel-induced mechanical allodynia. [46][47][48][49][50] We observed that CCL5 remained unchanged at the spinal cord level and was down-regulated in the DRG. Some previous studies have suggested that CCL5 up-regulation at the site of injury is a common determinant of neuropathic pain development.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, signi cant CCL2 rise over time and GM volume increase in dPCC were found in patients developing the CPTH, suggesting that the consistently observed associations of in ammation on PTH were at least partially attributable to their effect on GMV alternations. Taken together, the current study highlighted the role of the circulating CCL2 level in the pathogenesis and progression of PTH (48)(49)(50), and emphasized on the neuroin ammatory mechanism in morphological alternations associated with pain modulation in cognitive domain.…”
Section: Discussionmentioning
confidence: 57%
“…However, persistent activation of the microglial cells can elevate neuronal excitability and maintain the transmission of pain signals to the spinal dorsal horn neurons [12,13]. Indeed, the basis of neuropathic pain is the production of proinflammatory and pro-nociceptive mediators such as interleukins (IL-1β, IL-6, IL-12, IL-15, IL-18) [14], IFN-γ, TNF-α [15], and chemokines (CCL2, CCL3, CCL4, CCL5, CCL7) [16,17] by the constitutively active microglia cells [12,18,19]. The mitogen-activated protein kinase (MAPKs) family of proteins, including extracellular signal-regulated kinase (ERK), p38, and c-Jun N-terminal kinase (JNK), plays a crucial role in the signaling pathways mediating microglial activation and nociceptive responses, which eventually lead to neuropathic pain [20,21].…”
Section: Introductionmentioning
confidence: 99%